2019
DOI: 10.21315/aamj2019.24.s1.11
|View full text |Cite
|
Sign up to set email alerts
|

Are Muslims Practising Moderation in Their Financial Decisions?

Abstract: Statistics and a survey of the literature revealed the existence of a massive problem in the financial prudence of Malaysians, including Muslims. One glaringly prominent aspect is the absence of a spiritual/religious interventionist approach in exploring the lack of consumer awareness that led to the present situation. Instead of attempting to solve the problem through brute economic policies, a wasatiyyah-oriented approach is warranted for informing consumers of their religious obligation to avoid profligate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Financial literacy is imperative for sound financial decision making (Lusardi et al, 2010;Ramlee et al, 2019). Theoretically, financial literacy refers to an efficient financial plan that is reflected in an individual's saving, maintenance, and proper distribution of wealth for the later stage of life (Lusardi & Mitchell, 2008 ;Mahdzan & Victorian, 2013).…”
Section: Financial Literacy (Fl)mentioning
confidence: 99%
“…Financial literacy is imperative for sound financial decision making (Lusardi et al, 2010;Ramlee et al, 2019). Theoretically, financial literacy refers to an efficient financial plan that is reflected in an individual's saving, maintenance, and proper distribution of wealth for the later stage of life (Lusardi & Mitchell, 2008 ;Mahdzan & Victorian, 2013).…”
Section: Financial Literacy (Fl)mentioning
confidence: 99%
“…In addition, there are some exciting studies that focus on a particular group of respondents such as college students (Fazli Sabri et al, 2012), young employees (Abdullah et al, 2019;Mokhtar & Husniyah, 2017;Sabri & Zakaria, 2015), single mothers (Yuliandi et al, 2018), and Muslim individuals (Ramlee et al, 2019). Targeting respondents of a specific group will enable researchers to learn about the group's particular issues.…”
Section: Types Of Respondent and Psychological Variablesmentioning
confidence: 99%
“…These studies have the advantage of enabling researchers to arrive at an appropriate solution or action tailored to the respondent group. For example, the study by Ramlee et al (2019) about Malaysian Muslims found that the Muslims who practice moderation (Wasatiyyah) in their life will increase their financial well-being. The latest research was done by (Mahdzan et al, 2019) also shows a significant impact on financial well-being.…”
Section: Types Of Respondent and Psychological Variablesmentioning
confidence: 99%
See 2 more Smart Citations